Dissecting Patterns of Care in Patients With Variant Histology of Bladder Cancer and Lymph Node Invasion - Marco Bandini; Filippo Pederzoli; Andrea Necchi; Roger Li; Roberta Lucianò; Giuseppe Basile; Simone Scuderi; Riccardo Leni; Alberto Briganti; Andrea Salonia; Francesco Montorsi; Andrea Gallina; et al. (Société Internationale d’Urologie Journal)
Objectives: Lymph node invasion (LNI) is related to long-term survival in patients with muscle-invasive bladder cancer. However, in the case of variant histology (VH), data on pelvic lymph node dissection (PLND) and LNI are sparse. We described the pattern of care of PLND in patients with VHs of bladder cancer, exploring predictors of LNI. Methods: Using the 2001–2016 SEER registry, 20 767 bladder cancer patients who underwent PLND were identified. Included histological variants were pure urothelial carcinoma (UC), micropapillary UC, sarcomatoid UC, lymphoepithelioma-like UC, adenocarcinoma, sarcoma, giant and spindle cell carcinoma, squamous cell carcinoma (SCC), and neuroendocrine tumor. Uni- and multivariable logistic regression analyses tested for LNI predictors. Cox regression was used to test for predictors of overall mortality (OM) among both LNI positive and LNI negative patients. Results: Overall, 2464 (11.9%) harbored a VH. On multivariate analysis, only micropapillary UC was associated with higher risk (OR = 3.39) of LNI. This association was maintained when only the subset of patients treated without perioperative chemotherapy were analyzed (OR = 3.30). Similarly, higher T stage (T2 stage OR = 2.24; T3–4 stage OR = 9.44) and the use of chemotherapy (OR = 2.29) were associated with a higher risk of LNI. Among patients with LNI (5299, 25.5%), SCC (HR = 1.87), T3–4 stage (HR = 1.94), age at diagnosis (HR = 1.01) and geographic region (south) (HR = 1.22) were predictors of higher risk of OM. Conversely, chemotherapy (HR = 0.69) and number of removed LN (HR = −0.99) were associated with lower risk of OM. Finally, in a subgroup of patients without LNI, sarcomatoid UC (HR = 1.58) and giant and spindle cell carcinoma (HR = 1.83) were the only VH predictors of OM. Conclusions: We described different patterns of care in patients with VHs of bladder cancer. Micropapillary UC was an independent risk factor for LNI. Among patients harboring LNI, those with SCC VH had higher OM compared to pure UC. Conversely, sarcomatoid UC and giant and spindle cell carcinoma were predictors of OM in patients without nodal involvement.